Discerning coastal-process signatures and architectural styles in tidal barforms from the deltaic western Paleozoic Gondwana shoreline: new insights about the Balcarce Formation, Argentina - Olivo, Mariana Soledad (2024)
Sedimentological contrasts between coastal to shelf tidal barforms on ancient shorelines, particularly in tidally affected deltas, are relatively poorly understood. A comprehensive analysis of facies distribution and architectural attributes, complemented by virtual outcrop models (VOMs), has unveiled two different tidal barform archetypes in a sand-rich, tide-dominated deltaic succession in the lower Paleozoic Balcarce Formation, Argentina. Barform–channel type 1 comprises single packages of channel-bar units with inclined beds dipping to the N (paleolandward) and S (paleoseaward), composed predominantly of decimeter-scale planar cross-bedded sandstones. These deposits represent laterally migrating tidal bars. Barform–channel type 2, on the other hand, are multiple-stacked packages of sigmoidal inclined strata dipping to the NE (paleolandward) and SW (paleoseaward), consisting of conglomeratic sandstones with meter-scale trough cross-bedding. These strata depict tidal sand ridges exhibiting oblique accretion dynamics. Tidal barform–channel types 1 and 2 are not interspersed laterally and vertically, but they distinguish the lower and upper intervals of the Balcarce Formation. The lower interval shows full tidal control in barform–channel type 1. W-oriented flow of peak tidal currents completely reworked river-derived sediments and built the bar–trough morphology on the subaqueous platform of a tide-dominated delta. In the upper interval, tide- and river-generated facies alternate in barform–channel type 2. In this case, the higher fluvial input prevented complete tidal reworking. Thus, mouth-bardeposits were partially reworked into tidal ridges, which were organized in sandbanks extending across a tideinfluenced delta-front setting. A detailed comparison of tidal barform–channel types 1 and 2, together with a comprehensive re-evaluation of previously published basin-scale data, suggests that the coastal sector where Balcarce tidal barforms accumulated likely formed a strait connected to the open ocean to the east-southeast of the study area.